Baskakov-Kantorovich operators reproducing affine functions - BUSTAMANTE, Jorge (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
We present a new Kantorovich modification of Baskakov operators which reproduce affine functions. We present an upper estimate for the rate of convergence of the new operators in polynomial weighted spaces and characterize all functions for which there is convergence in the weighted norm. Mathematics Subject Classification (2010): 41A35, 41A36.